The Effect of Playdough Games on Developing Fine Motor Skills in 4-5 Year Old Children at Dharma Wanita Persatuan Pepelegi Kindergarten - Khania Mariska Putri Suharto; Aisyah (Universitas PGRI Madiun, 2026)
Playdough is a play material made from flour and is easy to make and safe for use by children—toys made from flour. As a medium, early childhood can train their fine motor skills. Playdough can be formed into various shapes, such as simple fruits. Playdough can provide opportunities for children. To develop their fine motor skills using creative, innovative, and fun methods. This study discusses the development of fine motor skills in children aged 4-5 years by using playdough as a tool. This study aims to explore how play with playdough can impact the fine motor skills of children aged 4-5 years at Dharma Wanita Persatuan Pepelegi Kindergarten. The approach used in this study is quantitative, with a research design that includes a pre-test and post-test in one group. The sample of this study involved all children aged 4 to 5 years at Dharma Wanita Persatuan Pepelegi Kindergarten, totaling 20 children. In this study, data were collected through test methods, observations, and recording. To test the proposed hypothesis, data analysis was carried out using the Paired Samples Test. The results of the analysis show the Sig. value. (2-tailed) of 0.000, which indicates that the results obtained are very significant.